Acute lower gastrointestinal bleeding due to low-grade mucinous neoplasm of appendix. Issue 5 (3rd September 2022) - Karatas, Murat; Simsek, Cenk; Gunay, Süleyman; Zengel, Baha; Okut, Gokalp; Yıldırım, Ali Murat; Vardar, Enver; Uslu, Adam
Abstract: Introduction: Lower gastrointestinal tract (GIT) bleeding originating from the appendix is rare and may be difficult to diagnose. Patients and methods: In this case report, we present an 88-year-old male patient who was admitted with hematochezia due to appendiceal bleeding. A colonoscopy revealed bleeding in the appendix orifice so an appendectomy was performed, and bleeding did not recur in the postoperative period. Results: The results of the microscopic examination showed low-grade mucinous neoplasm (LGMN) of the appendix. Conclusion: It should be kept in mind that bleeding may originate from the appendix in patients presenting with GIT bleeding. Our patient is the first to present with an acute lower GIT bleed who was diagnosed as having LGMN in the appendectomy specimen.